Potensi Biofisik Kawasan Konservasi sebagai Dasar Pengembangan Ekowisata Daerah Kabupaten Pesisir Selatan (Studi Kasus: Lubuk Larangan Bendung Sakti Inderapura) - Ira Desmiati; Siti Aisyah (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2023)
Currently Lubuk Larangan Bendung Sakti is expected to be gradually becoming an attractive tourist destination. There are several activities that can be done in ecotourism Lubuk Larangan Bendung Sakti which has the potential to become an ecotourism place. The purpose of this study is to examine how the development of ecotourism in Lubuk Larangan Bendung Sakti is assessed from A3 (Attractions, Accessibility, and Amenities) and biophysically the water quality of Lubuk Larangan Bendung Sakti waters in Pesisir Selatan Regency. The method used is descriptive quantitative with a score rating and followed by a water quality test using the STORET test. The results of the study indicate that the Biophysics viewed from the aspect of Attractions, Accessibility and Amenity in the Lubuk Larangan Bendung Sakti waters area belongs to the